GENDER PREDICTION BASED ON IRIS RECOGNITION - Ms.M.R.Rajput; Dr. G.S.Sable (International Journal of Innovations in Engineering Research and Technology, 2021)
As Iris is the most safe and reliable biometric pattern, Iris biometrics provides high recognition rate and high accuracy for person identification as compared with the other biometric techniques As Iris biometric only identify the identity a person , more research is needed to identify the gender , age and ethnicity based on iris textural and geometric features. Gender identification is equally important in critical security environment like Passenger control in airports ,access control in prohibited areas ,border control, database access, banking services. Major project undertaken by government of India that is Aadhar Project identify millions of citizens is also implemented with iris recognition. In literature most of the research is on gender identification based on facial images. Very few researchers reported gender identification based on human iris patterns